The socio-political construction and experience of corporate social responsibility (CSR): An investigation into the conflict surrounding the James Price Point LNG precinct, Kimberley, Western Australia - Wesley, Anthea (Curtin University, 2013)
This thesis proposes a new theoretical framework for analysing corporate social responsibility: the ‘spaces of CSR’, which draws together the concepts of governmentality and spatiality. This framework is applied to the case of the proposed LNG processing precinct at James Price Point in Western Australia to demonstrate how CSR is shaped by various forces within the political economy, and to explore the disparate ways in which CSR is experienced by the local community.